Digitalisasi dan Komunikasi Pertanian terhadap Pertumbuhan UMKM di Kecamatan Cipari Kabupaten Cilacap - Ernes Septina Azizi; Anggi Fitria Cahyaningsih; Faishal Permana; M. Aris Pujiyanto; Dwi Putriana N Kinding; Muhamad Solekan (Lembaga Pengembangan Kinerja Dosen, 2026)
The growth of agribusiness enterprises in Indonesia, particularly regarding digital technology access, barriers to technology adoption, operational efficiency, and business sustainability. The research employed a quantitative approach using a survey method through questionnaires distributed to agribusiness actors. Data were analyzed using descriptive quantitative analysis and ordinal logistic regression. The results indicate that digitalization positively influences the development of agribusiness enterprises in Indonesia. The use of digital technologies such as social media, agricultural marketplaces, digital farming applications, and the Internet of Things (IoT) has improved business communication effectiveness, expanded marketing access, accelerated market information access, and enhanced operational efficiency. The variable of digital technology access and utilization obtained an average score of 36.36, categorized as high, while the impact of digital utilization on business growth obtained an average score of 35.90, indicating positive benefits for most respondents. However, barriers such as limited internet infrastructure, low digital literacy, limited capital, and lack of technological assistance remain major challenges, with an average score of 31.20. The ordinal logistic regression analysis showed a probability value of 0.0135, indicating that the research model is statistically significant.